2017
DOI: 10.17159/1947-9417/2017/861
|View full text |Cite
|
Sign up to set email alerts
|

Changing educational traditions with the change laboratory

Abstract: This paper outlines the use of a form of research intervention known as the Change laboratory to illustrate how the processes of organisational change initiated at a secondary school can be applied to develop tools and practices to analyse and potentially re-make educational traditions in a bottom-up manner. In this regard it is shown how a culturalhistorical activity theory (CHAT) perspective can be combined with a relational approach to generate the theoretical and practical tools for managing change at a sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Grounded in CHAT, the Change Laboratory (CL) is a formative, interventionist, research methodology that allows participants to work jointly with a researcher-interventionist to shape an Activity System (Botha, 2017;Engeström & Sannino, 2010). Participants move from an individual position to develop collective transformative agency (Virkkunen, 2006), ultimately shaping their own activity system without the researcher-interventionist(s) (Morselli, et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Grounded in CHAT, the Change Laboratory (CL) is a formative, interventionist, research methodology that allows participants to work jointly with a researcher-interventionist to shape an Activity System (Botha, 2017;Engeström & Sannino, 2010). Participants move from an individual position to develop collective transformative agency (Virkkunen, 2006), ultimately shaping their own activity system without the researcher-interventionist(s) (Morselli, et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…As the results are promising, there is a need for more studies to be able to compare and draw general conclusions. While there are many studies using activity theory and expansive learning in the study of educational change (Botha 2017;Sannino 2008;Teräs and Lasonen 2013;Engeström et al 2002;Yamazumi 2008), few of these have been conducted on small-scale interventions, exploring the longitudinal development of expansive learning by analysing participants' discourse in the series of intervention sessions. This is needed and important to demonstrate evidence of expansive learning and the usability of CL interventions for educational change.…”
Section: Introductionmentioning
confidence: 99%
“…22-26) and its development (Postholm & Moen, 2011). This meeting place can support teacher education and practice, and it is suggested that Cultural Historical Activity Theory (CHAT) (Engeström, 2015(Engeström, , 2016Virkkunen & Newnham, 2013) offers conceptual tools that combine the necessary sources of expertise (Botha, 2017;Zeichner et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Various developmental studies using CHAT have addressed the importance of collaborative activity in such a meeting place (Botha, 2017;Engeström & Toiviainen, 2011;Postholm, 2008;Thorgeirsdottir, 2018). However, a search in Oria, with access to many databases with peer-reviewed journals, shows that few studies have focused on how such a meeting place could be developed at the beginning of a collaboration.…”
Section: Introductionmentioning
confidence: 99%